Determinants of Intention to Purchase Online Airline Ticket - alireza Hadadian; Amirhossein Bagherieh (تحقیقات بازار یابی نوین, 2014)
Nowadays development of information technology has caused online shopping continues to gain more acceptance by travelers that make airlines be care about factors affecting online ticket purchasing. Therefore, in this paper is an attempt to analyze intention to online airline ticket purchasing model according to trust, subjective norms, perceived risk, satisfaction and ease of use. The statistical population includes departure passengers of Mashhad international airport in domestic flights of September 2013 and sample size calculated for 215 passengers. Data collected by questionnaire that has appropriate validity and reliability. In addition, it is use structural equation model (SEM) and Lisrel8.8 Software to analyze hypothesis. The results show higher satisfaction and trust leads to more intention to online airline ticket purchasing. Moreover, perceived risk and ease of use have indirect effect on intention to online purchasing by trust and satisfaction and it is not support significant relationship between subjective norms and intention to online airline ticket purchasing.